Use of caffeine in 19,660 randomly selected U.S. adults: the role of overweight and obesity - Tucker, Larry A.; Beltran, Frank (Frontiers in Nutrition, 2025)
BackgroundCaffeine is a stimulant. It is one of the most consumed drugs in the United States. The present investigation was conducted to determine the relationships between BMI and waist circumference, and caffeine intake. The specific objective was to determine whether adults with higher BMIs or larger waist circumferences consume more or less caffeine than their counterparts.MethodsA sample of 19,660 randomly selected women and men, 20–75 years old, representing the U.S. adult population, was studied using a cross-sectional design. Data was collected as part of the National Health and Nutrition Examination Survey (NHANES) from 2009 through 2018. A number of covariates were controlled statistically to minimize their influence on the results: age, gender, race, year of assessment, alcohol use, smoking, time spent in moderate to vigorous physical activity, total energy intake (kcal), and consumption (g per 1,000 kcal) of dietary fiber, carbohydrate, protein, fat, sugar, and saturated fat.ResultsAfter adjusting for all the covariates, results showed that in U.S. men, there was a dose-response relationship between higher BMI categories and higher caffeine consumption (F = 4.1, p = 0.0092). After adjusting for all the covariates, the relationship between waist circumference and caffeine intake in men was linear (F = 8.0, p = 0.0060). In U.S. women, after adjusting for all the covariates, there was a weaker but significant relationship between the BMI categories and caffeine intake (F = 3.4, p = 0.0232). In women, the association between waist circumference and caffeine intake was not linear (F = 0.0, p = 0.8490), but was quadratic (F = 18.9, p < 0.0001) with all the covariates controlled.ConclusionsOverall, this study found that U.S. men with larger body mass and waist levels consumed higher amounts of caffeine than their counterparts. U.S. women did also, but the relationships were quadratic, not linear like the men's. It appears that the drug, caffeine, has multiple properties that appeal to adults with higher BMI and waist circumference levels. Additional research is needed to better understand why adults with larger body mass and waist sizes consume significantly more caffeine than their counterparts.